PSYCHOLOGICAL ENTRAPMENT AND SPATIAL POLITICS IN CHARLOTTE PERKINS GILMAN’S THE YELLOW WALLPAPER - Mohanad Naeem Hulaib (Universitas Islam Sumatera Utara (UISU), 2026)
This article examines the dialectical relationship between psychological entrapment and spatial politics in The Yellow Wallpaper to critique the domestic ideology of nineteenth-century America. The study explores how domestic and social spaces restrict women’s agency, ability, and well-being through patriarchal expectations embedded within the home. Using theories of psychological entrapment and spatial politics, the analysis focuses on the protagonist’s confinement in the nursery room, where surveillance, enforced isolation, and patriarchal control gradually lead to her psychological breakdown. The room and the yellow wallpaper symbolize the oppressive structures imposed on women, while simultaneously becoming sites of resistance. As the narrative progresses, the protagonist increasingly recognizes and resists the forces that confine her, culminating in the symbolic destruction of the wallpaper. The study argues that Charlotte Perkins Gilman transforms domestic space from a site of oppression into one of psychological and symbolic resistance. By connecting mental confinement with domestic spatial control, the article demonstrates how the story remains a significant feminist critique of patriarchal ideology and domesticity.